Donor Relation and Income Diversification Strategies of a Diocese in the Philippines - Christopher M. Villaronte; Joseph G. Guevarra (Philippine Social Science Journal, 2025)
To ensure long-term stability, religious organizations must supplement donations with diversified income sources. This descriptive-comparative study examined donor engagement and revenue strategies within a Negros Island Diocese to inform a Resource Mobilization Action Plan. Surveying 128 clergy and Parish Pastoral Council members, the study assessed donor relations and income generation using a validated questionnaire. While both groups indicated high implementation levels, significant perceptual differences emerged: lay members perceived a much greater extent of strategy application compared to the clergy. These findings highlight a critical need for better alignment and collaboration between ordained and lay leaders to promote unified financial sustainability. Beyond offering a model for reducing resource dependency, this research suggests future inquiries should explore longitudinal trends, technology’s role in donor engagement, and broader comparative studies to further strengthen non-profit financial stewardship.